Analisis Pengaruh Stabilisasi Tanah Lempung Lunak Menggunakan Bakteri Bacillus Subtilis dan Kapur Terhadap Nilai Parameter Fisis Tanah dan Kepadatan Tanah - Satria Jiro Jovian; Laily Endah Fatmawati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The development of infrastructure in Sidoarjo requires stable soil conditions, especially in areas dominated by soft clay soils. This study aims to determine the effect of soil stabilization using Bacillus subtilis bacteria and lime on the physical and compaction properties of soil. Laboratory tests were conducted on original soil and stabilized soil using 3% Bacillus subtilis bacteria with lime variations of 10% and 15% during a 3-day curing period. The results showed that the addition of Bacillus subtilis and lime reduced water content and optimum moisture content (OMC), while increasing the maximum dry density (MDD). The optimum mixture was obtained from 3% Bacillus subtilis and 15% lime, with an MDD value of 1.977 gr/cm³ and OMC of 19%. These results indicate that Bacillus subtilis and lime can improve soil density and stability. Therefore, this stabilization method has the potential to be applied as an alternative ground improvement technique for soft clay soils.